Analysis of Supply Chain Risk Management in The Lubricant Industry Using the House of Risk (HOR) Method - Muthia Putri Hidayati; Iwan Vanany (Jurnal Indonesia Sosial Teknologi, 2024)
PT.X is a company engaged in lubricant manufacturing. Based on the results of field studies, several risks hinder the company's supply chain process, and PT.X has never conducted a risk assessment. Therefore, risk analysis and mitigation are needed to minimize the risks that arise in the company's supply chain. This research uses the Supply Chain Operation Reference (SCOR) model to map the company's supply chain activities and the House of Risk (HOR) method to identify risks in the supply chain, including risk events, risk agents, and their correlations. The results reveal a total of 32 risk events and 26 risk agents. Then, a Pareto diagram calculation is conducted, identifying 3 priority risk agents that need to be addressed: supplier inability to provide raw materials, lack of work supervision, and inadequate workforce competence. From these 3 priority risk agents, 8 risk mitigation measures have been determined: evaluating supplier performance, establishing contracts with suppliers, planning alternative supplier selection, conducting periodic supervision, establishing company standard operating procedures, providing skills training and work discipline, recruiting workers more selectively and rigorously, and placing workers according to their expertise.